WEWENANG MAHKAMAH AGUNG MENGUJI KEABSAHAN PERATURAN DAERAH MELALUI HAK UJI MATERIIL - Kristianto, Simbar; Sinaulan, Ramlani Lina; Candra, Mardi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The regional government has the right to establish regional regulations and other regulations to implement regional autonomy and assistance tasks, this right is regulated in article 18 paragraph 6 of the 1945 Constitution,second amendment. The making of regional regulations in principle must be made based on nad guided by applicable laws and regulations. Regional regulationsare declared to have validity if the process of making them is based on 3 (three ) aspects, namely: authority, procedure and substance. Regional regulatios as an instrument of government are expected to provide benefits to achieve the goals of the state as stated in the 1945 Constitution. Although the making of regional regulations has good intentions and objectives, in practice there are citizens, communities, private legal entities and public legal entities who feel that their interest are harmed by the existence of these regional regulations. The provisions of article 24 paragraph 1 of the 1945 Constitution as amended in the third edition, stipulated that the Supreme Court has the authority to tes laws and regulatios under the law against the law. That according to the provisions of article 7 paragraph 1 of Law number 12 of 2011 concerning the formatios of law and regulations, the hierarchy of regional regulation is below the law. That thus the testing of the validity of regional regulations becomes the autorithy of the Supreme Court to tes it. The procedural law applicable to the examinations of the testing of laws and regulations under the law against the law is Supreme Court Regulations Number 1 of 2011 concerning the right to material review. That because there is a discrepancy between the material law and the proceduaral law governing the right to material review, it raises theproblem of hiw is the mechanism for testing the validity of regional regulations carried out by the Supreme Court ? The research in this thesis is in principle a normative research, so the approach chosen is legislative approach and cases approach; whilw the method used to analyze legal material or research data uses the deductive syllogism method. Testing the validity of regional regulations is in principle based on 3 ( Three ) aspects, namely: authority, procedure and substance. Thus testing these three aspects will begin with research on the basic regulations that regulate. Futhermore, to find out the applications of these regulatios in the practice of examining the to material review in the Supreme Court, it will be carried out on a sample of Supreme Court decisions that test the validity of regional regulations